Characterization of benign papillary thyroid carcinoma (PTC) in the Iraqi women - Mohammud Habash, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Papillary thyroid carcinoma (PTC) is a tumor malignancy observed commonly in the endocrine gland, comprises 75-85% of thyroid cancers. It predominately found in female; it is almost 2-3-fold higher than in male. The tumors in PTC are biologically lethargic and have exceptional prognosis. PTC is largely characterized by the presence of small or large thyroid nodules approximately having a maximum diameter of 10mm and detected in patients with benign thyroid goiter. Total thyroidectomy was preferred to treat PTC as it allows the correct risk assessment of the present tumor, depend on its size and provide safety to remove complete tissue with malignancy. The aim of the study is to characterize the benign PTC in Iraqi women. The study population consisted 6 patients with pathologically confirmed having papillary carcinoma (PTC). This study conducted in Al - Shafa hospital, Diyala, Iraq between January 2018 to January 2020. Seven female patients were recruited in the study aged between 20 to 60 years. Total thyroidectomy was performed after taking written consent for excision of lymph node. Present study was conducted on patients having palpable nodular swelling on their neck, while all the cases shown big thyroid nodule at the anterior side. women were included in the study, having minimum age of 20 years and maximum of 50 years. Total mean age recorded was 35 years. It suggests that, PTC was incident mainly in the middle age of adult life in women. Abnormal levels of thyroid hormones were detected. Total thyroidectomy was performed as a first line of treatment where benign single thyroid nodules were observed in histopathology analysis. Thus, Despite the increase in incidences of PTC, total thyroidectomy increases the survival rate and decrease the recurrence rate in studied cases. While its etiopathology is complex, further investigation is required so that it can be translated in clinical applications for diagnosis and treatment of cancer.